Moral thought after acquired cerebral damage. - Ramos-Galarza, Carlos (2018)
Introduction. Moral thinking is a mental skill that allows respecting implicit and explicit social norms. One factor that can alter its functioning is acquired brain damage, as is the case of subjects who have suffered a brain injury at the frontal lobe. Aim. To analyze the relationship between the process of moral thinking and brain functioning, through the description of cases that have suffered acquired brain damage, with the purpose of explaining the situation that an individual lives after presenting brain damage and becoming unable to respect social norms. Development. The clinic of patients who have suffered brain damage at the frontal level, such as Phineas Gage, NN and Elliot, is shown, in which it was observed that its state after the traumatic event was characterized by going back to previous stages of thinking moral, unlike a subject who may present brain damage in later structures. Conclusions. We discuss the analysis performed on the role of the frontal lobe in the process of respecting social norms that allow human interaction and how it can be affected by brain damage. © 2018 Fundacion para la difusion neurologica en Ecuador - FUNDINE. All Rights Reserved.